Urinary Sediment Transcriptomic and Longitudinal Data to Investigate Renal Function Decline in Type 1 Diabetes - Monteiro, Maria Beatriz; Pelaes, Tatiana S.; Santos-Bezerra, Daniele P.; Thieme, Karina; Lerario, Antonio M.; Oba-Shinjo, Sueli M.; Machado, Ubiratan F.; Passarelli, Marisa; Marie, Suely K. N.; Corrêa-Giannella, Maria Lúcia (Frontiers in Endocrinology, 2020)
Introduction: Using a discovery/validation approach we investigated associations between a panel of genes selected from a transcriptomic study and the estimated glomerular filtration rate (eGFR) decline across time in a cohort of type 1 diabetes (T1D) patients. Experimental Urinary sediment transcriptomic was performed to select highly modulated genes in T1D patients with rapid eGFR decline (decliners) versus patients with stable eGFR (non-decliners). The selected genes were validated in samples from a T1D cohort (n=54, mean diabetes duration of 21 years, 61% women) followed longitudinally for a median of 12 years in a Diabetes Outpatient Clinic. Results: In the discovery phase, the transcriptomic study revealed 158 genes significantly different between decliners and non-decliners. Ten genes increasingly up or down-regulated according to renal function worsening were selected for validation by qRT-PCR; the genes CYP4F22, LYPD3, and PMP22 were confirmed as differentially expressed comparing decliners versus non-decliners after adjustment for potential confounders. CYP4F22, LYPD3, PMP22, MAP1LC3C, HS3ST2, GPNMB, CDH6, and PKD2L1 significantly modified the slope of eGFR in T1D patients across time. Conclusions: Eight genes identified as differentially expressed in the urinary sediment of T1D patients presenting different eGFR decline rates significantly increased the accuracy of predicted renal function across time in the studied cohort. These genes may be a promising way of unveiling novel mechanisms associated with diabetic kidney disease progression.